Analisis Sosial Ekonomi Penumpang Bus Trans Donggala - Nurul Amalya Ahmadi; Eko Jokolelono (Penerbit Goodwood, 2025)
Purpose: This study analyzes the social and economic impacts of the Trans Donggala Bus as a mode of inter-city public transportation connecting Donggala Regency and Palu City. The objective is to evaluate its role in improving community mobility and economic welfare in regions with limited infrastructure. Methodology/approach: The research adopts a qualitative descriptive approach using surveys, in-depth interviews with stakeholders, and direct observations at the bus terminal. Data were grouped thematically to explore both social and economic dimensions of the bus service's impact. Results/findings: Findings reveal that the Trans Donggala Bus has had positive socio-economic effects. Socially, it enhances public access to education, health services, and markets in Palu City, reduces the rural-urban gap, and strengthens social interactions. Economically, it lowers transportation costs, allowing residents to reallocate funds for other household needs. Despite these benefits, challenges persist, including limited fleet numbers, insufficient route coverage, and inadequate terminal infrastructure, which hinder service efficiency. Conclusion: The Trans Donggala Bus has improved accessibility and reduced costs for communities, but optimization of routes, fleet expansion, and facility upgrades are needed to maximize its impact. Limitations: The study focuses solely on the Donggala–Palu route and uses qualitative methods limited to interviews and observations. Thus, it does not fully represent the views of the entire community across different areas. Contribution: This study highlights the importance of public transportation in enhancing mobility and economic resilience in underdeveloped regions. It also provides insights for local governments in developing sustainable and inclusive transport policies.